The effect of scaffolding inquiry-based STEM on problem-solving skills and creativity of prospective biology teacher students - Dita Purwinda Anggrella; Ahmad Kamal Sudrajat; Rahmania Pamungkas; Muhammad Kashif Majeed; Mohsin Rafique (University of Muhammadiyah Malang, 2026)
Background: Inquiry-based Biology learning requires adequate pedagogical support to foster the development of problem-solving skills and creativity among pre-service teachers. However, in the absence of structured guidance, students often experience difficulties in carrying out scientific inquiry processes. Integrating scaffolding within a STEM framework offers a promising approach to support more systematic and interdisciplinary learning. Objectives: This study aimed to examine the implementation of Scaffolding Inquiry-Based STEM and its association with students’ problem-solving skills and creativity in a Microbiology course. Methods: A mixed-methods approach with an embedded design was employed. The quantitative component used a one-group pretest–posttest design involving 15 students (n = 15), while qualitative data were collected through observations, interviews, and documentation to enrich the interpretation of the findings. Results: The results indicate improvements in problem-solving skills, particularly in problem identification, strategy application, reasoning, and evaluation. In addition, students’ creativity showed enhancement across multiple dimensions, including curiosity, fluency, originality, flexibility, elaboration, and risk-taking. Conclusion: These findings suggest that Scaffolding Inquiry-Based STEM is associated with the development of key 21st-century competencies among pre-service biology teachers. However, the absence of a control group limits the extent to which causal inferences can be drawn. Despite this limitation, the approach demonstrates potential for fostering more structured and meaningful Biology learning in higher education contexts.